Peran Kepala Sekolah Berbasis Mutu Pendidikan dalam meningkatkan Jumlah Peserta Didik Baru - Mustaqimah, Emi; Perawironegoro, Djamaluddin (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2024)
Educational quality-based leadership plays a key role in attracting new students to an educational institution. Quality-based leadership can increase the number of new students through superior programs such as BTQ, ICT learning, and education about batik. Improving the quality of education requires effective and efficient management of all institutional components, including educators, education staff, students, facilities and finance. Overall, effective leadership and quality educational programs have an important role in increasing the number of new students in an educational institution. The aim is to find out the role of school principals in increasing the number of students and to find out what programs can attract and attract new prospective students. The research method is qualitative, which is field research because the data produced is in the form of written or spoken words from objects and behavior that can be observed. The research results show that the quality-based leadership program in increasing the number of students at SD Muhammadiyah Wirobrajan 2 shows encouraging numbers in line with the targets to be achieved and satisfies education users.